Performances of Lokal Duck (Anas platyrhynchos Javanica)Fed Beluntas or Kenikir as Feed Additive - Lestari, D.; Rukmiasih, Rukmiasih; Suryati, T.; Hardjosworo, P. S. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2017)
Indonesia local duck has the potential to produce meat, but its growth is still slow. Therefore it needs the effort to improve the performance. One of the effort is using feed additive in the diet. Feed additive aimed to be appetizer and improve performance. Materials that can be used as feed additive are beluntas and kenikir because of their active compounds that can increase the appetite. This study aimedto examine the performances of local duck fed beluntas or kenikir as feed additive. The experimental design used was randomized design with 7 treatments and 5 replications. The treatment was the addition of beluntas or kenikir leaf meal in the diet during 1, 2or 3 weeks before being slaughtered. Variables observed were feed consumption, fenolik and tanin consumption, body weight, weight gain, percentage of carcass, chest, thigh, and abdominal fat. The results showed that the effects of beluntas or kenikir were not significant on performance (feed consumption, fenolik consumption, tanin consumption, body weight, and feed conversion) as well on carcass quality (carcass, abdominal fat, meat-bones of chest and thigh). Feeding beluntas or kenikir leaf meal 1% for 1, 2 or 3 week as feed additive did not improve the performances of local duck.